Early-life famine exposure, genetic susceptibility and risk of MAFLD in adulthood - Yuying Wang; Kun Zhang; Bin Wang; Bowei Yu; Ziteng Zhang; Yuetian Yu; Yuefeng Yu; Ying Sun; Yi Chen; Wen Zhang; Yan Cai; Qian Xiang; et al. (The Journal of Nutrition, Health and Aging)
Objectives: Early-famine exposure was reported to be associated with metabolic associated fatty liver disease (MAFLD); however, it has not been fully elucidated whether the gene-famine interaction exist in this association. We aimed to investigate the association between early-life famine exposure in different genetic risk stratifications and the risk of MAFLD in adulthood. Design, setting, participants, and measurements: The study included 8213 participants from the SPECT-China study. Famine exposure subgroups was defined according to the birth year. A genetic risk score (GRS) was constructed with single nucleotide polymorphisms associated with MAFLD in East Asians. Logistic models were used to examine the association of famine exposure and GRS with MAFLD. Results: Early-life famine exposure was positively associated with MAFLD after adjusting for multiple confounders (OR (95% CI): fetal-exposure 1.3(1.11−1.53), childhood exposure 1.12(1−1.25)). Meanwhile, with per SD increment of GRS (2.49 points), the OR(95%CI) of MAFLD was 1.1(1.04−1.16). In high GRS group, fetal-exposure was positively associated with 45% higher risk of MAFLD (1.45(1.15–1.83)). In men, neither in low or high GRS subgroups observed an association between early-life famine exposure and MAFLD. But in women with high GRS of MAFLD, fetal-exposure was positively associated with even higher risk of MAFLD (1.64(1.22–2.22)). Conclusion: The positive association between early-life famine exposure and MAFLD is intensified by high genetic susceptibility of MAFLD in women and in general population in China; while this association does not exist in men or in those with low genetic risk scores.